Airway clearance, mucoactive therapies and pulmonary rehabilitation in bronchiectasis. Issue 3 (16th January 2019) - O'Neill, Katherine; O'Donnell, Anne E.; Bradley, Judy M.
ABSTRACT: This paper aims to provide physiological rationale for airway clearance, mucoactive therapy and pulmonary rehabilitation (PR) (or exercise interventions) in bronchiectasis. There is increasing emphasis on the role of airway clearance techniques (ACT) in the management of bronchiectasis. No single ACT has currently shown superior effect over another. Given the large range of different techniques available, consideration of the physiological effects underpinning a technique including expiratory flow, ventilation and oscillation, is essential to effectively personalize ACT. Key clinical trials of mucoactives in bronchiectasis are underway and will provide clarity on the role of these agents in the management of patients with bronchiectasis. Prescription of mucoactive therapies should be done in conjunction with ACT and therefore the mechanism of action of mucoactive drugs and their timing with ACT should be taken into consideration. PR and/or exercise training are recommended in all current bronchiectasis guidelines. There is a clear physiological rationale that muscle weakness and physical inactivity may play a role in disease progression as well as impacting health‐related quality of life, frequency of pulmonary exacerbations and ability to mobilize sputum. However, there are residual unanswered questions surrounding the delivery and accessibility to PR. This review summarizes the physiological principles and supporting evidence for airway clearance, mucoactive medication and PR, which are key components in the management of bronchiectasis.